2022
DOI: 10.1002/aenm.202202074
|View full text |Cite
|
Sign up to set email alerts
|

Surface and Defect Engineering Coupling of Halide Double Perovskite Cs2NaBiCl6 for Efficient CO2 Photoreduction

Abstract: amounts of greenhouse gases, leading to global warming. Widely distributed solar energy is the most abundant and cleanest energy on the earth. Therefore, the conversion of carbon dioxide into renewable hydrocarbons through solar light-driven photocatalysts is an effective strategy to mitigate the environmental crisis. [1,2] Photocatalytic materials have been widely developed since Fujishima's pioneering research work on photocatalytic decomposition of water was reported in 1972. [3] However, single-component s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(38 citation statements)
references
References 61 publications
(57 reference statements)
1
37
0
Order By: Relevance
“…The effect of bandgap on W incorporation was studied by UV–vis diffuse reflectance and the results are shown in Figure a; the Bi 2 MoO 6 and Bi 2 WO 6 have absorption edges of 480 and 440 nm, and calculated bandgap energy of 2.65 and 2.83 eV respectively (eq S4). Upon introducing W, the absorption edges of Bi 2 Mo 1– x W x O 6 solid solutions show the redshift, but the change is very minimal and the results correlate well with previous reports. ,, Moreover, the CBM and VBM of Bi 2 Mo 1– x W x O 6 solid solutions were calculated (eqs S5–S6) from results of Mott–Schottky plots (Figure S7) and XPS valence band analysis , (Figure S8) and results are given in Figure c and Table S3, which indicates that when the small amount of Mo replaced by W there is no appreciable change in the band structure; meanwhile, it suggests that the influence of W is higher in the conduction band states than the valence band, which is further confirmed by the band structure analysis using DFT calculations. The DFT results clearly explain that the VBM of the Bi 2 MoO 6 and Bi 2 WO 6 mainly consists of O-2p and Bi-6s orbitals and CBM mainly originated from Mo-4d or/and W-5d orbitals, respectively.…”
Section: Results and Discussionsupporting
confidence: 86%
“…The effect of bandgap on W incorporation was studied by UV–vis diffuse reflectance and the results are shown in Figure a; the Bi 2 MoO 6 and Bi 2 WO 6 have absorption edges of 480 and 440 nm, and calculated bandgap energy of 2.65 and 2.83 eV respectively (eq S4). Upon introducing W, the absorption edges of Bi 2 Mo 1– x W x O 6 solid solutions show the redshift, but the change is very minimal and the results correlate well with previous reports. ,, Moreover, the CBM and VBM of Bi 2 Mo 1– x W x O 6 solid solutions were calculated (eqs S5–S6) from results of Mott–Schottky plots (Figure S7) and XPS valence band analysis , (Figure S8) and results are given in Figure c and Table S3, which indicates that when the small amount of Mo replaced by W there is no appreciable change in the band structure; meanwhile, it suggests that the influence of W is higher in the conduction band states than the valence band, which is further confirmed by the band structure analysis using DFT calculations. The DFT results clearly explain that the VBM of the Bi 2 MoO 6 and Bi 2 WO 6 mainly consists of O-2p and Bi-6s orbitals and CBM mainly originated from Mo-4d or/and W-5d orbitals, respectively.…”
Section: Results and Discussionsupporting
confidence: 86%
“…To solve this problem, some Pb-free perovskite QDs have been obtained, such as Cs 2 SnI 6 , 126,127 Cs 2 AgBiX 6 , 128 and Cs 2 NaBiCl 6 . 129 Nonetheless, the photocatalytic CO 2 activities of these substitutions are lower than that of Pb-based perovskite QDs. As a result, much attention should be paid to finding stable low-toxic or non-toxic perovskite materials with high catalytic performance.…”
Section: Challenges and Opportunitiesmentioning
confidence: 99%
“…However, defects are inevitable in the process of preparing materials, which signicantly inuence the photovoltaic performance of materials. 30 On one hand, the local energy levels introduced by the defects can modulate the energy band structure and enhance the light absorption of semiconductor materials; on the other hand, defects can act as electron capture centers, provide electrons on the material surface, and promote the separation of photogenerated electron-hole pairs. 31,32 Yue et al reported that Cs 2 AgBiBr 6 with bromine (Br)-vacancy exhibits strong stability, the defects could optimize its electronic structure and enhance charge separation, leading to improved photocatalytic performance.…”
Section: Introductionmentioning
confidence: 99%